Fisetin-induced cell death in human ovarian cancer cell lines via zbp1-mediated necroptosis - Yaxian Liu; Hongwen Cao; Yanhui Zhao; Lijuan Shan; Shuhai Lan (BMC, 2022)
Abstract Background Among reproductive cancers, ovarian cancer leads to the highest female mortality rate. Fisetin, a natural flavonoid, exerts pharmacological effects, inhibiting cancer growth with various origins. Although multiple mechanisms are involved in regulating cell death, it is still unclear whether and how fisetin exhibits anticancer effects on ovarian cancer. The present study aimed to evaluate cell apoptotic and necroptotic processes occurring in ovarian carcinoma (OC) cell lines induced by fisetin. Methods Cell growth was evaluated by MTT assay in OC cell lines treated with or without fisetin. Annexin V/propidium iodide staining followed by flow cytometry was used to characterize fisetin-induced cell death. The apoptotic process was suppressed by z-VAD intervention, and cell necroptosis was assessed by introducing ZBP1-knockdown OC cell lines coupled with fisetin intervention. The expression of necroptosis-related mediators and the migration capability of the respective cells were evaluated by Western blotting and in vitro cell invasion assay. Result Fisetin successfully reduced cell growth in both OC cell lines in a dose-dependent manner. Both apoptosis and necroptosis were induced by fisetin. Suppression of the cell apoptotic process failed to enhance the proliferation of fisetin-treated cells. The induced cell death and robust expression of the necroptotic markers RIP3 and MLKL were alleviated by knocking down the expression of the ZBP1 protein in both OC cell lines. Conclusion The present study provided in vitro evidence supporting the involvement of both apoptosis and necroptosis in fisetin-induced OC cell death, while ZBP1 regulates the necroptotic process via the RIP3/MLKL pathway.